Dynamics and control analysis during rendezvous in non-Keplerian Earth—Moon orbits - Innocenti, Mario; Bucchioni, Giordana; Franzini, Giovanni; Galullo, Michele; Onofrio, Fabio D’; Cropp, Alexander; Casasco, Massimo (Frontiers in Space Technologies, 2022)
The paper describes the development of a framework capable of addressing some fundamental issues in the analysis of proximity operations between two spacecraft that are operating within a three-body model defined by two primaries and the spacecraft themselves. The main objective is to enable the capability of analysing dynamic and control issues during an automated rendezvous between a vehicle and a passive space station orbiting around the Earth - Moon L2 Lagrangian point on a near rectilinear halo orbit. The paper presents first a restricted three body model dynamics and a nominal approach trajectory, followed by an analysis of the influence of assumed actuators and sensors. Critical aspects such as selected failures are investigated, in order to ensure passive safety of the mission using impulsive maneuvers. An example of closed loop guidance in the near range is also presented and the overall performance are validated with an Ephemeris model available in the literature.